Evaluasi Investasi dan Profitabilitas Pascapanen Lada Putih: Studi Kasus Efisiensi Manajemen Air Perendaman - Dicky Aditya Warman; Elfani Devitasari; Nur Rizqi Bariroh (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
This study aims to evaluate the investment feasibility and analyze the profitability of white pepper processing businesses through an approach focusing on the efficiency of water management in the soaking process. The research method employed is a quantitative approach, utilising a case study of a white pepper processing business unit in Kutai Kartanegara Regency. The analysis was conducted using financial feasibility parameters, including Net Present Value (NPV), Net Benefit-Cost Ratio (Net B/C), Internal Rate of Return (IRR), and Payback Period (PP). The results of the study indicate that all treatments have a positive NPV, a Net B/C ratio greater than one, an IRR exceeding the interest rate, and a relatively short payback period. Efficiency in the management of soaking water plays a crucial role in reducing operational costs and enhancing product value. Consequently, the white pepper processing business is deemed financially viable and holds prospects for sustainable development. This study contributes to the development of an integrative model combining post-harvest technical aspects with economic analysis within the agro-industrial sector